A twin chamber up-flow bio-electrochemical pumparound system for sequential nitrification and denitrification of reject water. Issue 44 (19th September 2016) - Mousavi, Seyyed Alireza; Ibrahim, Shaliza; Aroua, Mohamed Kheireddine
Abstract: In this study, a modified twin chamber up-flow bioelectrochemical reactor (TCUBER) was investigated during sequential bioelectrochemical nitrification and denitrification of reject water experimentally. A twin chamber up-flow bioelectrochemical pump-around system (TCUBEPS) makes it possible to investigate the effects of different pH values (6.5 ± 0.1, 7.5 ± 0.1, 8.5 ± 0.1, and 9.5 ± 0.1) on the system efficiency at different applied current intensities ( I  = 20–50 mA) and HRT (6–24 h) values. The results show that the pump-around system succeeded to stabilize the pH and the most favorable values of pH for the activation of nitrifying and denitrifying bacteria in both compartments were 7.5 and 8.5, respectively, whereas the removal percentage of NH4 -N was 96% at higher applied HRT (24 h) and constant I (50 mA). This study contributed to a better understanding of the function of variables, namely HRT, pH, and I to treat reject water with high concentration of ammonium.